Constructivism for English Language Teaching in The 21st Century in The Indonesian Context: Library Research - Jasrial, Dedi; Zaim, M (Edu-Ling: Journal of English Education and Linguistics, 2023)
In Indonesia's English language education, adapting constructivist principles for the 21st century involves acknowledging the diversity of learners' backgrounds, learning styles, and the impact of technology. This study aims to explore the impact of technology integration in the implementation of constructivist approaches, ways constructivist principles be adapted or modified to cater to the diverse students’ backgrounds, and innovative and effective assessment methods that align with constructivist philosophy in English language teaching in Indonesia in the 21st century.  This research used library research in which the data were collected using library materials, and ten article journals. The data were analyzed qualitatively using the content analysis technique. The results show that the impact of technology integration in the implementation of constructivist approaches in English language teaching in Indonesian classrooms in the 21st Century included a vast array of authentic and diverse English language materials, enabling teachers to create immersive and engaging learning environments. Additionally, The ways in which constructivist principles can be adapted or modified to cater to the diverse students’ backgrounds in Indonesian English language classrooms include acknowledging and valuing linguistic diversity, incorporating various learning styles, sociocultural experiences, and collaborative and cooperative learning strategies. Moreover, innovative assessments applied included authentic assessment, formative assessment, project-based assessment, and technology-enhanced assessment. In conclusion, constructivist philosophy highly benefits English language teaching in the Indonesian context in the 21st Century. Keywords: constructivism, English language teaching, technology integration, diverse students’ background, innovative assessment system